Thrust evaluations of masonry domes. An application to the St. Peter's dome. (2019) - Como, Mario
The research of the thrust of the St. Peter's dome has a long history that goes up to Poleni (1748) and to the so-called Three Mathematicians (1742) which, in the first half of the 18th century, were engaged to study the damaged dome and to provide its strengthening and restoration. The paper recalls this history and in the framework of some developments of limit analysis applied to masonry bodies, gives an evaluation of the thrust of the St. Peter's dome in Rome by using the kinematical approach.